Stakeholder-led project management : changing the way we manage projects - Worsley, Louise M. (New York, New York (222 East 46th Street, New York, NY 10017) : Business Expert Press, 2017)
If stakeholders matter, then their impact should affect the way we plan, execute and implement projects. Most projects--and all valuable projects--have stakeholders, and require some form of stakeholder engagement. It is the engagement that needs managing, not the stakeholders, because the right type of engagement varies depending on the types of stakeholders involved and the context of the project. This book provides a stakeholder-centered analysis of projects, and explains which identification, analysis, communication and engagement models are relevant to different types of projects: from an office move, to IT enterprise changes, to transformational change of business, to complex social change. Using case studies from around the world, it illustrates what goes wrong when stakeholders are not engaged successfully, and what lessons we can learn from these examples. Three main cases are used to demonstrate the application of stakeholder analysis and modelling tools, leaving the reader with a very practical understanding of which techniques may be beneficially applied on their own projects.
1. Stakeholder-neutral to stakeholder-led projects -- 2. Stakeholder identification -- 3. Understanding my stakeholders -- 4. Changing the way we manage projects -- 5. Communicating in projects -- 6. Developing the engagement plan -- 7. The principles of engagement -- Index.
Includes bibliographical references and index.
Title from PDF title page (viewed on March 3, 2017).
Electronic reproduction. Ann Arbor, MI : ProQuest, 2016. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Project management; Project management; Program management; Stakeholder engagement; Stakeholder management; Project governance; Project communication; Sociodynamic model; Salience model; Electronic books